Immune versus thrombotic stimulation of platelets differentially regulates signalling pathways, intracellular protein-protein interactions, and alpha-granule release - Rex, Sybille; Beaulieu, Lea M; Perlman, David H; Vitseva, Olga; Blair, Price S; McComb, Mark E; Costello, Catherine E; Freedman, Jane E (Thrombosis and haemostasis, 2009)
In addition to haemostasis, platelets mediate inflammation and clearance of bacteria from the bloodstream. As with platelet-platelet interactions, platelet-bacteria interactions involve cytoskeletal rearrangements and release of granular content. Stimulation of the immune Toll-like receptor 2 (TLR2) on the platelet surface, activates phosphoinositide-3-kinase (PI3K) and causes platelet activation and platelet-dependent thrombosis. It remains unknown if platelet activation by immune versus thrombotic pathways leads to the differential regulation of signal transduction, protein-protein interactions, and alpha-granule release, and the physiological relevance of these potential differences. We investigated these processes after immune versus thrombotic platelet stimulation. We examined selected signalling pathways and found that phosphorylation kinetics of Akt, ERK1/2 and p38 differed dramatically between agonists. Next, we investigated platelet protein-protein interactions by mass spectrometry (MS)-based proteomics specifically targeting cytosolic factor XIIIa (FXIIIa) because of its function as a cytoskeleton-crosslinking protein whose binding partners have limited characterisation. Four FXIIIa-binding proteins were identified, two of which are novel interactions: FXIIIa-focal adhesion kinase (FAK) and FXIIIa-gelsolin. The binding of FAK to FXIIIa was found to be altered differentially by immune versus thrombotic stimulation. Lastly, we studied the effect of thrombin versus Pam(3)CSK(4) stimulation on alpha-granule release and observed differential release patterns for selected granule proteins and decreased fibrin clot formation compared with thrombin. The inhibition of PI3K caused a decrease in protein release after Pam(3)CSK(4)- but not after thrombin-stimulation. In summary, stimulation of platelets by either thrombotic or immune receptors leads to markedly different signalling responses and granular protein release consistent with differential contribution to coagulation and thrombosis.